2017
DOI: 10.1242/jcs.196303
|View full text |Cite
|
Sign up to set email alerts
|

JunB regulates angiogenesis and neurovascular parallel alignment in mouse embryonic skin

Abstract: Blood vessels and nerve fibers are often closely arranged in parallel throughout the body. Therefore, neurovascular interactions have been suggested to be important for the development of vascular networks. However, the molecular mechanisms and genes regulating this process remain unclear. In the present study, we investigated the genes that are activated in endothelial cells (ECs) following interactions with neurons during vascular development. Microarray analyses of human primary microvascular ECs co-culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Infil‐trating inflammatory cells such as monocytes, endothelial cells, and local matrix degradation might be sources of VEGF that can increase alveolar capillary permeability. Recently, Yoshitomi et al () reported that VEGF was up regulated in JunB‐over expressing endothelial cells, suggesting that VEGF is induced by JunB. Additionally, AP‐1 an intracellular transcription activator, binds to the promoter region of the VEGF gene (Lee et al, ) and upregulates VEGF expression in different cancers (Bancroft et al, ; Chen, Chen, Pang, Hu, & Zhang, ; Yin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Infil‐trating inflammatory cells such as monocytes, endothelial cells, and local matrix degradation might be sources of VEGF that can increase alveolar capillary permeability. Recently, Yoshitomi et al () reported that VEGF was up regulated in JunB‐over expressing endothelial cells, suggesting that VEGF is induced by JunB. Additionally, AP‐1 an intracellular transcription activator, binds to the promoter region of the VEGF gene (Lee et al, ) and upregulates VEGF expression in different cancers (Bancroft et al, ; Chen, Chen, Pang, Hu, & Zhang, ; Yin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analyses were performed as described previously (Yoshitomi et al, 2017). Briefly, total RNA was extracted using TRIZOL reagent (Invitrogen) and was purified using RNeasy Mini kits (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Lentiviral vector production was performed as described previously (Yoshitomi et al, 2017). Briefly, the human Otx2 (RefSeq NM_001286481.1) open reading frame was amplified using RT-PCR using primers listed in and was cloned into pCDH vectors (System Biosciences, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate directional expansion in both structures depends on common repulsive and attractive cues such as neuropilins, ephrins, and JunB. 8,[11][12][13] Additionally, nerves locally generate vascular endothelial growth factors, crucial angiogenesis and lymphangiogenesis stimulators, and vessels supply artemin and neurotrophin 3, key mediators attracting axons. 8,[14][15][16] Shared growth cues and bidirectional communication could explain why disorganized vascular growth found in facial VANs impacts patterning of FN branches.…”
Section: Introductionmentioning
confidence: 99%